Peningkatan Kompetensi Manajemen Usaha Tani Melalui Pelatihan Pembukuan Usaha Tani Di Kampung Koya Koso Distrik Abepura Kota Jayapura Provinsi Papua - Rachmaeny Indahyani; La Maga; Hijrah Irawan; Mimin Lewonama (The Community Engagement Journal, 2023)
Any costs allocated by farmers will directly affect the amount of revenue and the level of income or profits of farmers. The thing that must be understood is to find out the size of the costs incurred in farming each planting season, it takes a source of information related to the costs incurred, selling prices and the amount of production in farming. The source of information referred to is farming bookkeeping, farming bookkeeping will provide information for farmers about the development of farming activities every planting season. In explaining their farming, the participants never took notes and even compiled books in their farming. farmers in Koya Koso generally do not manage their farming costs well. Farmers understand that land preparation costs and planting costs are the total costs or total costs in farming. While the cost of using tools in farming needs to be taken into account, because basically the tools used in farming have a limited economic life. After farmers understand and are able to distinguish between fixed costs and variable costs in farming, the next activity is to provide training to farmers to calculate the amount of revenue and income. In general, farmers consider the value of the sale is the net profit received in one growing season. So this training provides an understanding to farmers about the differences in income and income.Keywords: Competence, management, farming, farming bookkeeping